Original Items and Imitations of Classical Antiquity in Isabella d’Este’s Grotta - Makho, Olga G. (Actual Problems of Theory and History of Art, 2015)
Isabella d’Este’s (1474–1539) collection of fine art, which she kept gathering for years, and housed in her private apartments, in a premise known as Grotta, nearby her studiolo, was to a great extent focused on Classical antiquity. Thanks to the preserved documents, the collection, though dispersed as early as in late 1620s, is renowned. Despite the variety of items in the collection, the owner’s interests were primarily aimed to replenish it with pieces connected with Classical antiquity. Isabella’s special attention was paid to acquisition of Greek and Roman antiquities, and she endeavoured seriously to reach the goal. As a result the collection contained coins and medals, gems and sculptures dating back to those times. Large group of contemporary items consisted not only of pieces that were thematically based on Classical subjects, but also presented reproduced variants of well-known antique sculptures. Those were neither casts, nor copies of the originals, but they help us understand the specificity of originals’ interpretation by the artists of the Renaissance, whose skills were aimed to create exhibits for collections of this kind.